Rancang Bangun Repository Publikasi Dosen di Universitas Negeri Manado Menggunakan Metode Waterfall - Fadly Iriansyah (Program Studi Teknik Informatika, 2024)
Scientific publications and research are essential aspects of the development of science. Lecturer's scientific publications are also a requirement for accreditation and will be a continuous assessment cycle in the assessment of study programs at UNIMA. LPPM UNIMA has the task of managing the publications of each lecturer, but the collection of lecturer publications is still operated manually. LPPM must contact the lecturers individually to hand in the publication, which is recorded in Excel and archived in the LPPM storehouse. These problems prompted the creation of a repository at UNIMA to facilitate the management of lecturer publications and to present recapitulation reports for lecturer publications development. The repository uses the Waterfall method from the analysis, design, and coding to the testing stages. The system modeling is documented, namely Data Flow Diagrams (DFD). The testing method of the repository uses the Black-box testing method so that it can answer and show that the repository was created pursuant to the objectives of the researcher and is able to meet user needs.